Working / Still : 14 Purchase College Photographers. - Cohen, John; Devine, Jed; Hagen, Charles; Neuberger Museum of Art, State University of New York (New York : Purchase College SUNY, 1997)
Baer, Adam ; Crewdson, Gregory ; Deluise, Regina ; Frampton, Jerald ; Guarino, Lois ; Hunt Currier, Ann ; Kozma, Robert ; Licht, Adam ; McGlynn, David ; Modica, Andrea ; Neal, Albert ; Newton, robert ; Richter, Curt ; Wang, Harvey
Neuberger Museum of Art, New York, June 7 - September 28, 1997
kunstcatalogus